Comprehensive Pharmacognostical and Phytochemical investigation of Leucomeris spectabilis leaves using GC–MS analysis - Chaudhary, Ramesh Pratap; Mani, Munesh (Journal of Neonatal Surgery, 2025)
The leaves of Leucomeris spectabilis are used in folk medicine as a crude drug in the treatment of diabetes. This present work deals with Pharmacognostical studies such as Qualitative, quantitative, powder microscopy of Leaf, physicochemical studies, phytochemical studies, thin layer chromatography and GC-MS analysis of Leucomeris spectabilis leaves for future prospect. Pharmacognostical, phytochemical, and GC-MS analysis are used to screen, identify, extract, and isolate phyto-constituents in order to assess the therapeutic potential of the plant and to define phytochemical standards for medicinal plant materials for quality control purposes